Characterization of the piRNA pathway during development of the sea anemone Nematostella vectensis. Issue 12 (2nd December 2017) - Praher, Daniela; Zimmermann, Bob; Genikhovich, Grigory; Columbus-Shenkar, Yaara; Modepalli, Vengamanaidu; Aharoni, Reuven; Moran, Yehu; Technau, Ulrich
ABSTRACT: PIWI-interacting RNAs (piRNAs) and associated proteins comprise a conserved pathway for silencing transposons in metazoan germlines. piRNA pathway components are also expressed in multipotent somatic stem cells in various organisms. piRNA functions have been extensively explored in bilaterian model systems, however, comprehensive studies in non-bilaterian phyla remain limited. Here we investigate the piRNA pathway during the development of Nematostella vectensis, a well-established model system belonging to Cnidaria, the sister group to Bilateria. To date, no population of somatic stem cells has been identified in this organism, despite its long life-span and regenerative capacities that require a constant cell-renewal. We show that Nematostella piRNA pathway components are broadly expressed in early developmental stages, while piRNAs themselves show differential expression, suggesting specific developmental roles of distinct piRNA families. In adults, piRNA associated proteins are enriched in the germline but also expressed in somatic cells, indicating putative stem cell properties. Furthermore, we provide experimental evidence that Nematostella piRNAs cleave transposable elements as well as protein-coding genes. Our results demonstrate that somatic expression of piRNA associated proteins as well as the roles of piRNAs in transposon repression and gene regulation are likely ancestral features that evolved before the split between Cnidaria and Bilateria.